Gain clamped L-band EDFA using a fiber Bragg grating in two stage configuration - Harun, Sulaiman Wadi; Tamchek, Nizam; Ahmad, Harith (John Wiley & Sons, 2003)
A gain clamping technique for the long-wavelength-band erbium-doped fiber amplifier (L-band EDFA) is presented. If uses two circulators and a fiber Bragg grating (FBG) to route a backward amplified spontaneous emission (ASE) from a second-stage amplifier and launch it back into the first stage. The use of a broadband (BB) FBG has shown a better gain clamping effect, compared to a narrowband (NB) FBG. The amplifier gain for the BB FBG set up is clamped at 15.0 dB with a gain variation of less than 0.1 dB for an input power as high as -5 dBm. The use of a BB FBG has also flattened the gain spectrum.